Film induced tourism: a study on the potential of film induced tourism to motivate travelers - Tari, Laleh Khalili (2012)
Now a day in modern society, movies play an enormous role in human beings everyday life. We would accost some movie being awaited with great expectations and some others that they are not at the center of attention but they would be a big hit after being released. The Lord of the Rings trilogy is the example of such case. Many people went to the movies to see the trilogy since it was extremely popular and the audience really liked them. In addition to that the movies were also drowned in various awards and prizes not many other movies have gained. This subject is not studied much and there are just a few studies on movie-induced tourism therefore, this thesis includes subjects that are not much being focused on before and as a result, it might sound interesting and challenging to the audience. This thesis tries to fill some gaps and find connections between them in order to understand the process of film-induced tourism better. Destination image, travel motivation, authenticity and travel behavior in a film tourism context were examined areas. An interest in being a film tourist was noted, but the activity could take many forms and the trip did not essentially have to go to the film location. It was also found that the view of legitimacy both in a film viewing and a tourism background is subjective, but the film tourist doesn’t want to reiterate his/her idea of authenticity. It was recommended that film tourists oblige personal meanings on places before visitation with different range of indications. It is said that many tourists are afraid of disappointment they come across within the process of film location visiting. It is quite undeniable that both tourism and entertainment industries are growing day by day and they have an increasing influence on their consumer. Film-induced tourism is an observable fact considering those industries. We cannot find so many films being produced with the purpose of encouraging people to visit specific destinations. However consumers would be ready to invest money to see and experience a scene being recorded in film. Both film and television series have been extensively considered as being able to create representation of destinations all over the world. The audience could watch the places, people and stories that a film is built up and when a feature stands out it can be encouraging enough for a viewer to travel to the film location to make the connection himself.